Shared Genetic Links Between Nonalcoholic Fatty Liver Disease and Coronary Artery Disease - Hua Di; Shouhao Wang; Chengan Xu; Qiaoqiao Yin; Keyang Xu; Wei Zheng (Global Heart)
Background: Epidemiological and clinical studies have shown that there is a co-morbidity between nonalcoholic fatty liver disease (NAFLD) and coronary artery disease (CAD). Methods: In this study, we utilized linkage disequilibrium score regression (LDSC) to evaluate the genetic correlation between non-alcoholic fatty liver disease (NAFLD) and coronary artery disease (CAD). We identified pleiotropic loci and genes using SNP-Level PLACO analysis. Following this, MAGMA gene set enrichment analysis was conducted to assess the biological significance of these pleiotropic genes. Finally, a two-sample two-way Mendelian randomization (MR) analysis was performed to evaluate causal relationships between NAFLD and CAD. Results: We found a significant genetic correlation between NAFLD and CAD. Secondly, PLACO multi-effect analysis identified 6 sites (mainly involved in the establishment of chylomicrons, mitochondrial membrane protein localization and herpes simplex virus 1 infection signaling pathway). Then, three pleiotropic genes (APOC1, TOMM40 and PBX4) were identified by MAGMA gene analysis. Finally, a two-sample two-way MR analysis suggested that there was no causal relationship between NAFLD and CAD. Conclusions: Our results show that there are significant gene overlaps and pleiotropic genes between NAFLD and CAD and point out their common molecular mechanisms. These findings provide evidence for the common etiology between them and also help to better understand the pleiotropic nature between NAFLD and CAD, which may be of guiding significance for future treatment strategies.